Repeated trans-arterial treatments of LDL-DHA nanoparticles induce multiple pathways of tumor cell death in hepatocellular carcinoma bearing rats - Wang, Yuzhu; Li, Junjie; Vale, Goncalo Dias do; Chaudhary, Jaideep; Anwar, Arnida; McDonald, Jeffrey G.; Qin, Tao; Zhang, Hongwei; Corbin, Ian R. (Frontiers in Oncology, 2022)
Introduction Repeated hepatic arterial delivery of therapeutic agents to the liver by percutaneously implanted port-catheter systems has been widely used to treat unresectable liver cancer. This approach is applied to assess the therapeutic efficacy of repeated low-density lipoprotein-docosahexaenoic acid (LDL-DHA) nanoparticle treatments in a rat model of hepatocellular carcinoma. Methods N1S1 hepatoma bearing rats underwent placement of a percutaneously implanted hepatic artery port-catheter system and were allocated to untreated, control LDL-triolein (LDL-TO) or LDL-DHA nanoparticle infusions groups. Treatments were performed every three days over a nine day study period. MRI was performed at baseline and throughout the study. At the end of the study tissue samples were collected for analyses. Results and Discussion Implantation of the port catheters was successful in all rats. MRI showed that repeated infusions of LDL-DHA nanoparticles significantly impaired the growth of the rat hepatomas eventually leading to tumor regression. The tumors in the LDL-TO treated group showed delayed growth, while the untreated tumors grew steadily throughout the study. Histopathology and MRI support these findings demonstrating extensive tumor necrosis in LDL-DHA treated groups while the control groups displayed minor necrosis. Molecular and biochemical analyses also revealed that LDL-DHA treated tumors had increased levels of nuclear factor-kappa B and lipid peroxidation and depletion of glutathione peroxidase 4 relative to the control groups. Evidence of both ferroptosis and apoptosis tumor cell death was observed following LDL-DHA treatments. In conclusion repeated transarterial infusions of LDL-DHA nanoparticles provides sustained repression of tumor growth in a rat hepatoma model.